Conjuring cognition: a review of educational magic-based interventions - Wiseman, Richard; Watt, Caroline (PeerJ, 2020)
For hundreds of years, magic tricks have been employed within a variety of pedagogic contexts, including promoting science and mathematics, delivering educational messaging, enhancing scepticism about the paranormal, and boosting creative thinking for product design. This review examines this diverse body of work, focusing on studies that have assessed the impact of such interventions. Although the studies tended to yield positive outcomes, much of the work suffered from methodological shortcomings, including measuring the impact of interventions over a relatively short period of time, focusing on self-report measures and failing to employ control groups. The paper makes several recommendations for future study in the area, including assessing the longer-term impact of magic-based interventions, comparing these interventions to other types of pedagogic techniques, focussing on knowledge retention and behavioural outcomes, and collaborating with magicians to develop more impactful interventions.
Keywords: Magic; Psychology; Education; Cognition; Belief; Science; Critical thinking; Conjuring; Pedagogic